Nighttime vertical plasma drifts and the occurrence of sunrise undulation at the dip equator: A study using Jicamarca incoherent backscatter radar measurements - Ambili, K. M. (2013)
The absence of photoionization, in combination with sustained downward plasma motion at night, means that the F region can be severely depleted at the magnetic equator in the morning. As a result, at sunrise, there can be a sudden upward jump in altitude of the F region peak followed by a quick descent in association with the downward motion of the photoionization production peak. This constitutes what is known as the equatorial sunrise undulation. Its anecdotal existence has been reported over Jicamarca while it has been seen repeatedly over Trivandrum, India, during equinox conditions. By contrast, we find that the phenomenon is not as frequent at Jicamarca as at Trivandrum. Using incoherent backscatter radar data from Jicamarca, we show that the differences have an electrodynamical origin. The sunrise undulation gets masked when remnant plasma from the previous night does not move down to low enough altitude. The nighttime residual ion density and its altitude are found to be strongly influenced by the evening and nighttime electric field. There is a strong association between a strong plasma uplift at sunset and the appearance of an undulation at sunrise around the magnetic equator.